High-Performance Liquid Chromatography Quantitative Determination of Oxyresveratrol and Morin Contained in Maclura cochinchinensis Extract and Gel Formulation - Vongsak, Boonyadist; Petchsomrit, Arpa (Engineering Tribology and Biomedical Materials, 2021)
Maclura cochinchinensis (Lour.) Corner., of the Moraceae family, is a medical shrub commonly found in Thailand, and for which a wide variety of pharmacological activities have been reported, including antiviral, anti-inflammatory, antioxidant, and anticancer activities. The main bioactive compounds, oxyresveratrol and morin, are known to be found in M. cochinchinensis heartwood. In this study, we quantitatively analyzed the levels of these two active substances in M. cochinchinensis extracted with various solvents, including in various cosmetic formulations and herbs sourced from various parts of Thailand. High-performance liquid chromatography (HPLC) was performed on a C18 column with an isocratic elution using 1.5% formic acid and acetonitrile at a flow rate of 1 ml/min, and detected at 352 nm. This method was validated for accuracy, precision, linearity, limits of detection, and quantification. The average percent recovery for oxyresveratrol and morin in the extracts was 100.01 ± 0.62% and 99.31 ± 2.56%, and in gel formulation was 99.65 ± 3.54% and 118.41 ± 4.70%, respectively. The relative standard deviation of intra- and inter-day precision was less than 2.0% and 2.8%, respectively. Limits of detection and quantification were 0.06 and 0.2 μg/ml, respectively. The amounts of oxyresveratrol and morin extracted from different solvents, such as acetone, 80% ethanol, 50% ethanol, methanol, and distilled water were in the range of 37.75–68.16 and 54.63–144.83 mg/g, respectively, while five samples of M. cochinchinensis heartwood collected from different regions of traditional drug stores contained in the range of 26.85–60.37 and 110.26–157.44 mg/g, respectively. Additionally, the percentage label amounts of oxyresveratrol and morin were analyzed in gel preparations, and found at 82.88% and 120.99%, respectively. This technique is convenient, simple, and reliable to effectively analyze the content of these active compounds in extracts and cosmetic products.